The Influence of Macroeconomic Factors and Global Commodity Prices on the Jakarta Islamic Index (JII) in Indonesia with the VECM Approach - Nofrianto Nofrianto; Wilda Hanifah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the influence of macroeconomic factors and global commodity prices on the prices of sharia stocks that are members of the Jakarta Islamic Index (JII) in Indonesia, using monthly data for the period January 2011-December 2024 as many as 168 observations. The variables used include inflation, BI Rate, rupiah exchange rate, money supply (M2), world gold price, and world oil price. Data was obtained from BPS, Bank Indonesia, Indonesia Stock Exchange, World Gold Council, and U.S. Energy Information Administration (EIA). The Vector Error Correction Model (VECM) method is used to identify short-term and long-term influences. The results show that in the long term, gold prices and world oil prices have a significant positive effect on JII, while the rupiah exchange rate and the money supply have a significant negative effect. Inflation and the BI Rate do not have a significant influence. In the short term, the ECT value of −0.038970 indicates an adjustment towards a long-term equilibrium of 3.9% per period. The novelty of this research lies in the use of a longer data range until 2024 and the simultaneous integration of domestic macro and global commodity variables in the VECM model, thus providing a more comprehensive picture of the behavior of the sharia stock market after the pandemic. Practically, these findings are important for investors and policymakers to understand JII's sensitivity to global factors, especially world gold and oil price movements, in order to optimize investment strategies and stability of the Islamic capital market. Keywords: Jakarta Islamic Index, Macroeconomics, Gold Price, World Oil Price, VECM.